Rapid dipstick detection of Vibrio cholerae in household stored and municipal water in Dhaka, Bangladesh: CHoBI7 trial. Issue 2 (14th November 2016) - Rashid, Mahamud‐ur; Rahman, Zillur; Burrowes, Vanessa; Perin, Jamie; Mustafiz, Munshi; Monira, Shirajum; Saif‐Ur‐Rahman, K. M.; Bhuyian, Sazzadul Islam; Mahmud, Md. Toslim; Sack, R. Bradley; Sack, David; Alam, Munirul; et al.
Abstract: Objective: In urban Dhaka, Bangladesh, 30% of source water samples collected from the households of patients with cholera had detectable Vibrio cholera e. These findings indicate an urgent need for a public health intervention for this population. The Crystal VC ® dipstick test is a rapid method for detecting V. cholerae in stool and water. However, to date no study has investigated the use of the rapid dipstick test for household surveillance of stored drinking water. Methods: The efficacy of the Crystal VC ® dipstick test for detecting V. cholerae in the Dhaka city municipal water supply and stored household drinking water sources after enrichment for 18 h in alkaline peptone water (APW) was compared to bacterial culture as the gold standard. Results: A total of 1648 water samples (824 stored household drinking water samples and 824 municipal water supply samples) were collected from households of patients with cholera. The overall specificity and sensitivity of the dipstick test compared to bacterial culture was 99.6% (95% confidence interval (CI): 99.2%, 99.9%) and 65.6% (95% CI: 55.2%, 75%), respectively. The specificities for stored household drinking water and Dhaka city municipal supply water compared to bacterial culture were 99.8% (95% CI: 99.1%, 100%) and 99.5% (95% CI: 98.6%, 99.9%), respectively ( P = 0.138), and the sensitivities were 66.7% (95% CI: 43.0%, 85.4%) and 65.3% (95% CI: 53.5%, 76.0%), respectively ( P = 0.891). Conclusion: The Crystal VC ® dipstick is a promising screening tool for cholera outbreak surveillance in resource‐limited settings where elimination of false‐positive results is critical. The lower than expected sensitivity should be further investigated in future studies.